Promoting Sikhi among Malaysian youth: A case study of the Sikh Naujawan Sabha Malaysia (SNSM). (2nd October 2018) - Kaur, Arunajeet
ABSTRACT: The Sikh Naujawan Sabha Malaysia (SNSM) has been an important vehicle in keeping the tenets of the Sikh faith alive for the Malaysian Sikh community. It is primarily a Sikh youth organization, initiated with the blessings of the Malaysian Sikh community elders in the 1960s, who decided that starting the activity of prayer and contemplation on Sikhi was crucial from a young age. Over the decades, the SNSM has been adept in evolving its activities and organization to cater to the altering needs and self-conceptions of the various generations of Sikh youth. This paper documents the trajectory of SNSM activities and reinvention to cater to the generations of Sikhs post-Independence.